The overall cesarean hysterectomy - Arana Arana, Julio (2015)
It has conducted a study on 45 cases of cesarean hysterectomy Total operated by the author in the Department of Gynecology and Obstetrics of the General Hospital Cayetano Heredia Base, and the results obtained in this series with 4,598 cases reported in the world literature compared. Some innovations made to the classical surgical technique is described, with special mention in the operative steps in order to decrease intra-operative bleeding. Anesthesia and spinal election was overall combination.